Toxicity of lignans to symbiotic fungus of leaf-cutting ants - Pagnocca, F. C.; Ribeiro, S. B.; Torkomian, VLV; Hebling, MJA; Bueno, O. C.; DaSilva, O. A.; Fernandes, J. B.; Vieira, P. C.; DaSilva, MFDGF; Ferreira, A. G. (Plenum Publ Corp, 1996)
Lignans from Virola sebifera Aubl., Virola sp., and Otoba parvifolia (Mkfg.) A. Gentry (Myristicaceae) inhibited the in vitro growth of the fungus cultivated by leaf-cutting ants of the species Atta sexdens rubropilosa Forel (Hymenoptera: Formicidae). A comparison of activity among the lignans was obtained.
Keywords: lignans; leaf-cutting ants; antifungal compounds; Virola sebifera; Otoba parvifolia; Atta sexdens rubropilosa